Effect of PCI on QTC Dispersion in Patients with Angina - Islam, Md Shafiqul; Mondal, Shekhar Kumar; Jahan, Jafrin; Arefin, Minhaj; Ahmed, Nishat; Das, Pinaki Ranjan; Azam, MG (University Heart Journal, 2020)
Background:‘Coronary heart disease (CHD) is now the leading cause of death worldwide; it is on the rise and has become a true pandemic that respects no borders. For the diagnosis of coronary artery disease, the 12 leads electrocardiogram (ECG) is the most readily available noninvasive test by which, in addition of diagnosis, localizing and estimating the size of myocardial ischemia can be determined. Abnormally high QT dispersion has been correlated with risk of arrhythmic death in various cardiac diseases including CAD. An increase in QTd is reported to predict the occurrence of life-threatening ventricular tachyarrhythmias and sudden cardiac death in patients with ischemic heart disease. Materials and Methods: This Cross sectional analytical study was conducted in Department of Cardiology, National Institute of Cardiovascular Diseases, Dhaka from January 2013 to December 2013. A total of 100 consecutive patients with angina based on predefined enrollment criteria were included in the study. .All patients were evaluated by history, clinical examination, biochemical analysis, and coronary angiogram (CAG) which was performed during index hospital admission. PCI was done only if the vessel was significantly stenosed.i,e. for LMCA - e”50%, for LAD, LCX and RCA it was e”70% as significant stenosis. Severity of stenosis of the involved vessels were categorized as severe( e”90%) and moderate(<90%). Results: Among the study population 76 (76%) patients were male and 24 (24%) patients were female. The left anterior descending artery (LAD) group comprised 37 patients and there were significant differences between before and after PCI QTc dispersion (90.5±38.9 vs 70.4±39.6 ms, p=0.001). The left circumflex artery (LCX) group was comprised of 6 patients and there were significant differences between before and after PCI QTc dispersion (62.2±41.9 vs 50.2±37.2 ms, p=0.001). The right coronary artery (RCA) group consisted of 18 patients, there being significant differences between before and after PCI QTc dispersion (84.9±40.7 vs 69.1±41.5 ms, p=0.001) Conclusion: PCI reduces QTc dispersion significantly among patients with angina. This QTc dispersion change is not influenced by sex, smoking, beta-blockers, hypertension, diabetes, renal impairment, stable or unstable angina but it depends upon the severity of coronary artery stenosis, involvement of coronary vessel and number of vessels.Reduction of QTc dispersion is a good sign of successful PCI that indicates successful reperfusion which carries an excellent prognostic value of revascularization.Further long term follow up will establish it. University Heart Journal Vol. 16, No. 1, Jan 2020; 33-39